2011
DOI: 10.1016/j.cellimm.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Induction of polyclonal CD8+ T cell activation and effector function by Pertussis toxin

Abstract: Pertussis toxin (PTX) has pronounced adjuvant activity and strongly enhances innate and adaptive immune responses, including increased antibody production and Th1/Th2 cytokine production. Adjuvant effects of PTX on Th1 and Th2 cells are primarily mediated via CD80/86 costimulation via enhanced expression of these molecules by APCs. However, it has remained unresolved whether PTX modulates the expression of costimulatory and inhibitory molecules on CD4+ and CD8+ T cells. To address this question, we determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
4
0
3
Order By: Relevance
“…The cytokine hyperresponsiveness in Gα i2 ‐knockout mice was subsequently shown to be due to abnormal T‐cell receptor signaling (72). Although this finding suggests a direct role for PTX in regulating T‐cell effector responses and some studies have suggested a direct effect of PTX on T cells (73), including increased expression of CD28 paralleled by up‐regulation of CD69 and induction of IFN‐γ, granzyme B, and IL‐17 (74), the preponderance of the data suggests that PTX acts indirectly on T cells by activating APCs and up‐regulating CD80, CD86, and major histocompatibility complex class II expression (5863).…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine hyperresponsiveness in Gα i2 ‐knockout mice was subsequently shown to be due to abnormal T‐cell receptor signaling (72). Although this finding suggests a direct role for PTX in regulating T‐cell effector responses and some studies have suggested a direct effect of PTX on T cells (73), including increased expression of CD28 paralleled by up‐regulation of CD69 and induction of IFN‐γ, granzyme B, and IL‐17 (74), the preponderance of the data suggests that PTX acts indirectly on T cells by activating APCs and up‐regulating CD80, CD86, and major histocompatibility complex class II expression (5863).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its action on CD4 + T cells, PTX induces the activation of CD8 + T cells [97]. PTX strongly upregulates the expression of CD28 by CD8 + T cells, but not by CD4 + T cells, as well as the expression of CD69, IFN-γ, IL-17, and granzyme B by purified CD8 + T cells in a CD80-and CD86-dependent manner.…”
Section: Role Of Ptx In Pathogenesis and Action On Immune Cellsmentioning
confidence: 98%
“…É possível que a PT apresente um mecanismo semelhante ao das toxinas colérica (CT -produzida por Vibrio cholerae) e termo-lábel (LT -produzida por E. coli), que também são exotoxinas heterohexamericas do tipo AB 5 . Estas toxinas, CT e LT, além de ter uma ação toxica semelhante ao da PT, também atuam como um imunógeno e adjuvante de mucosa induzindo IgG e IgA contra antígenos co-administrados por via nasal, oral ou parental (Holmgren, Adamsson, 2005 e CD69 e na expressão de IFN-γ, granzima B e IL-17 (Murphey, Chang et al, 2011). In vitro foi demonstrado que a PT é capaz de estimular a expressão das moléculas coestimulatorias CD40, CD83e CD86 e do MHC classe II em células dendríticas (Wang, Yang, 2006 Assim, em nosso modelo, a atividade enzimática de PT também parece não ser essencial para a ação adjuvante.…”
Section: Discussionunclassified
“…Além disso a PT foi capaz de aumentar a expressão de moléculas co-estimulatórias na superfície de células B, macrófagos e linfócitos T (Ryan, McCarthy, 1998). Estudos mais recentes mostram que a ação adjuvante de PT envolve estimulação e maturação de células apresentadoras de antígenos (APC) e ativação de linfócitos T CD8 + (Murphey, Chang, 2011).…”
Section: Introductionunclassified